A Xanthomonas campestris pv. campestris protein similar to catabolite activation factor is involved in regulation of phytopathogenicity. - de Crecy-Lagard, V (J Bacteriol, 1990)
A DNA fragment from Xanthomonas campestris pv. campestris that partially restored the carbohydrate fermentation pattern of a cya crp Escherichia coli strain was cloned and expressed in E. coli. The nucleotide sequence of this fragment revealed the presence of a 700-base-pair open reading frame that coded for a protein highly similar to the catabolite activation factor (CAP) of E. coli (accordingly named CLP for CAP-like protein). An X. campestris pv. campestris clp mutant was constructed by reverse genetics. This strain was not affected in the utilization of various carbon sources but had strongly reduced pathogenicity. Production of xanthan gum, pigment, and extracellular enzymes was either increased or decreased, suggesting that CLP plays a role in the regulation of phytopathogenicity.